Assessment of the effect of using intrauterine platelet-rich-plasma on the success of assisted reproduction: a systematic review and meta-analysis of randomized controlled trials - Alkhamis, Fatimah Hussain (International Journal Of Community Medicine And Public Health, 2024)
Intrauterine administration of platelet-rich-plasma (PRP) has shown potential in improving pregnancy outcomes in assisted reproductive technology (ART). However, the efficacy of PRP in enhancing clinical pregnancy and live birth rates remains a topic of debate. This meta-analysis evaluated the effectiveness of intrauterine PRP administration in improving clinical pregnancy and live birth rates. A systematic search of electronic databases was conducted to identify randomized controlled trials (RCTs) comparing intrauterine PRP administration with control in women undergoing ART. The primary outcomes were clinical pregnancy rates and live birth rates. Data were extracted and pooled using a random-effects model to calculate odds ratios (ORs) with 95% confidence intervals (CIs). Heterogeneity was assessed using the I² statistic. Nineteen RCTs involving 1,918 participants were included for clinical pregnancy rates, and six RCTs involving 777 participants were included for live birth rates. The pooled OR for clinical pregnancy rates was 2.49 (95% CI: 1.84, 3.35), indicating a significant improvement in the PRP group. For live birth rates, the pooled OR was 3.28 (95% CI: 1.18, 9.09), also favouring the PRP group. Moderate heterogeneity was observed for clinical pregnancy rates (I²=43%), while substantial heterogeneity was observed for live birth rates (I²=77%). Funnel plots showed no significant publication bias for either outcome. Intrauterine PRP administration significantly improves clinical pregnancy and live birth rates in women undergoing ART. The pooled ORs of 2.49 for clinical pregnancy rates and 3.28 for live birth rates support the potential clinical utility of PRP in enhancing ART outcomes.